The Outcomes of Radiosurgery for Arteriovenous Malformations—Experience of a Tertiary Cancer Center from India - Sanjay M. Hunugundmath; Sumit Basu; Bhooshan Zade; Vikram Maiya; Rahul Sharma; Ashok Bhanage; Sathiyanarayanan Vatyam (Indian Journal of Neurosurgery)
Objectives This article assesses the treatment outcomes in the patients diagnosed with arteriovenous malformations (AVMs) treated with stereotactic radiosurgery. Materials and Methods We retrospectively analyzed 30 patients diagnosed with AVM treated between 2010 and 2018.The median age at presentation was 30 years (range: 14–60 years). The median planning target volume (PTV) was 6.8 mL (range: 0.9–54 mL). The median dose prescribed was 18 Gy (range: 16–24 Gy). Modified radiosurgery-based AVM grading score was calculated for all the patients. Results The median follow-up of the entire cohort was 60 months (range: 24–96 months). The obliteration rates for patients followed up for 3 and 5 years were 75 and 86.1%, respectively. Age (< 35 years; p = 0.007) and PTV (< 7 mL; p = 0.04), had better obliteration rates. Three patients had hemorrhage, from the AVM after irradiation. None of them were fatal. Conclusion Stereotactic radiosurgery is a preferred noninvasive treatment modality with acceptable morbidity.